2021
DOI: 10.1177/03000605211000506
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shock index-based risk indices for predicting in-hospital outcomes in patients with ST-segment elevation myocardial infarction undergoing percutaneous coronary intervention

Abstract: Objective We aimed to determine whether the prognostic value of the shock index (SI) and its derivatives is better than that of the Thrombolysis In Myocardial Infarction risk index (TRI) for predicting adverse outcomes in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI). Methods A total of 257 patients with STEMI undergoing primary PCI from January 2018 to June 2019 were analyzed in a retrospective cohort study. The SI, modified shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Prior studies have demonstrated the prognostic utility of SI in patients with individual cardiac pathologies, including ACS, heart failure, and cardiogenic shock [ 31 35 ]. SI alone was shown to perform as well as the GRACE risk score in patients with ACS, with the advantage of being easier to calculate [ 36 38 ]. Notably, both HR and SBP are included in the GRACE risk score [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated the prognostic utility of SI in patients with individual cardiac pathologies, including ACS, heart failure, and cardiogenic shock [ 31 35 ]. SI alone was shown to perform as well as the GRACE risk score in patients with ACS, with the advantage of being easier to calculate [ 36 38 ]. Notably, both HR and SBP are included in the GRACE risk score [ 7 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…shown to perform as well as the GRACE risk score in patients with ACS, with the advantage of being easier to calculate [36][37][38]. Notably, both HR and SBP are included in the GRACE risk score [7,39].…”
Section: Plos Onementioning
confidence: 96%
“…Multivariate analysis shows that high SI (and its derivatives) values are associated with higher complication rates. 19 Renal dysfunction is believed to be a risk factor for mortality in patients with myocardial infarction. 4 Cywinski et al showed that estimated renal function was a better prognostic indicator than Scr.…”
Section: Discussionmentioning
confidence: 99%
“…Although evaluation of SI derivatives is less frequently investigated in HF, there are several records that assessed the utility of these indices in acute coronary syndrome (ACS), especially myocardial infarction (MI) patients. 29 - 32 A study on 24 636 subjects suffered from ACS with optimal SI cut-off point of 0.80 showed patients who had higher values experienced 3.40 times (95% CI: 2.29-5.02, P < .001) increased chance of in-hospital death compared to those with lower SI ranges. 33 …”
Section: Discussionmentioning
confidence: 99%